Adipocyte Hyperplasia Facilitated Adipose Tissue Expansion to Alleviate Hepatopancreas Injury in Nile Tilapia (Oreochromis niloticus) Fed High-Fat Diet - Senyue Tan; Jiamin Wei; Ailan Diao; Douglas R. Tocher; Zeling Lin; Bing Chen; Ruixin Li; Shuqi Wang; Cuiying Chen (Aquaculture Nutrition, 2025)
Previous studies showed that interplay between liver and adipose tissue was important for animals to adapt to high-fat diets (HFDs). While the mechanisms of adaptation to HFD are not fully understood in fish, we hypothesize that interaction between these key tissues will be crucial. The present study evaluated the physiological and biochemical characteristics and gene expression profiles of hepatopancreas and adipose tissue of Nile tilapia (Oreochromus niloticus; initial weight, 20.01 ± 0.01 g) fed diets containing either 6% lipid (normal-fat diet [NFD]) or 12% lipid (HFD) for up to 10 weeks. While growth was not affected, serum and hepatopancreatic lipid contents increased significantly in tilapia fed HFD compared to fish fed NFD at 6 weeks (p <0.05). In addition, feeding HFD for 6 weeks induced hepatopancreatic injury as shown by increased alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities in serum and higher expression of genes related to inflammation (tnfβ and il-1β) and malondialdehyde (MDA) content in hepatopancreas (p <0.05). However, after feeding HFD for 10 weeks, serum and hepatopancreatic lipid contents and injury indices decreased, whereas mesenteric fat index (MFI) and expression of genes related to glucose (GLU) metabolism (pfk, g6pd, and glut2) in hepatopancreas increased significantly compared to the NFD group (p <0.05). Significant expansion of mesenteric adipose tissue was observed in tilapia fed HFD, due mainly to adipocyte hypertrophy at 6 and 8 weeks and hyperplasia at 10 weeks. With the expansion of mesenteric adipose tissue, the expression of genes related to lipid metabolism and inflammation increased at 8 weeks, but decreased at 10 weeks. The data indicated that excess dietary lipid accumulated initially in hepatopancreas of tilapia consuming HFD, but prolonged intake promoted mesenteric adipose tissue development, potentially mitigating hepatopancreas damage caused by excess lipid deposition. Additionally, enhanced hepatopancreatic glycolysis may contribute to the adaptation of tilapia to HFD intake.